PERFIL EPIDEMIOLÓGICO Y QUIRÚRGICO DE PACIENTES NEURO-ONCOLÓGICOS SOMETIDOS A CIRUGÍAS NEUROLÓGICAS - Jamilly Nunes Moura; Mary Elizabeth de Santana; Ingrid Magali de Souza Pimentel; Maria da Conceição Nascimento Freitas; Jamil Michel Miranda do Vale; Suelen Gaia Epifane; Lucimário Valente Ferreira (Universidade Federal do Paraná, 2021)
Objective: to investigate the sociodemographic and surgical profile of neuro-oncology patients subjected to neurological surgeries. Method: a descriptive and retrospective study with a quantitative approach, conducted during a five-year period (2014-2018) in a hospital with 236 beds, which is a reference in cancer treatment in the state of Pará. The data were collected from September to December 2019 and analyzed by means of descriptive statistics. Results: the profile was characterized by the age group of 41 to 50 years old (30.8%; n=20) and by individuals with complete elementary school (44.6%; n=29). They were subjected to elective surgeries (87.7%; n=57), considered clean (95.4%; n=62), and large (96.9%; n=63). The main complications were surgical site infection (10.7%; n=8) and tumors located in the encephalus (60%; n=39). Conclusion: the paper contributed to delineate the profile of the population served by the hospital, enabling the expansion of debates aimed at improving hospital planning and at refining the quality of the health services and of the Nursing assistance.